Endoplasmic Reticulum-Associated Degradation-Dependent Processing in Cross-Presentation and Its Potential for Dendritic Cell Vaccinations: A Review - Jun Imai; Sayaka Ohashi; Takahiro Sakai (MDPI AG, 2020)
While the success of dendritic cell (DC) vaccination largely depends on cross-presentation (CP) efficiency, the precise molecular mechanism of CP is not yet characterized. Recent research revealed that endoplasmic reticulum (ER)-associated degradation (ERAD), which was first identified as part of the protein quality control system in the ER, plays a pivotal role in the processing of extracellular proteins in CP. The discovery of ERAD-dependent processing strongly suggests that the properties of extracellular antigens are one of the keys to effective DC vaccination, in addition to DC subsets and the maturation of these cells. In this review, we address recent advances in CP, focusing on the molecular mechanisms of the ERAD-dependent processing of extracellular proteins. As ERAD itself and the ERAD-dependent processing in CP share cellular machinery, enhancing the recognition of extracellular proteins, such as the ERAD substrate, by ex vivo methods may serve to improve the efficacy of DC vaccination.